HUBUNGAN POLA ASUH ORANG TUA DENGAN SIBLING RIVALRY PADA ANAK USIA SEKOLAH KELAS V DAN VI SD DARUL FAIZIN - Tedi Irawan, Ade; Agustini, Aat; Nur Fadillah, Annisa (STIKES HUSADA GEMILANG, 2025)
Sibling Rivalry is likely influenced by parents, whether causing it or helping to cope with it. Parenting is the first education for children, the first time they become acquainted with the world, born into a family environment educated by their parents. The role model of parents in daily actions becomes a medium for moral education for children, shaping them to be social and religious beings to create conditions that foster initiative and creativity in children. This study aims to determine the relationship between parenting styles and Sibling Rivalry in fifth and sixth-grade students at Darul Faizin Elementary School. The type of research is quantitative, with a cross-sectional design. The sample consists of 30 students from fifth and sixth grades. Data was collected using parenting style and Sibling Rivalry questionnaires. The results showed that less than half (43.3%) of fifth and sixth-grade elementary school children received a neglectful (permissive) parenting style, while more than half (56.7%) experienced Sibling Rivalry. It can be concluded that there is a relationship between parenting styles and Sibling Rivalry in children of fifth and sixth-grade at Darul Faizin Elementary School (p-value = 0.02). It is hoped that parents will attend counseling on child-rearing so they can understand good parenting styles for the proper growth and development of their children. Sibling Rivalry kemungkinan dipengaruhi oleh orang tua, baik yang menyebabkan maupun membantu dalam mengatasinya. Pola asuh adalah pendidikan pertama bagi anak, pertama kalinya mereka mengenal dunia, terlahir di lingkungan keluarga yang dididik oleh orang tua. Keteladanan orang tua dalam tindakan sehari-hari menjadi wahana pendidikan moral bagi anak, membentuk anak sebagai makhluk sosial, religius untuk menciptakan kondisi yang menumbuhkan inisiatif dan kreatifitas anak. Penelitian ini bertujuan untuk mengetahui hubungan pola asuh orang tua dengan Sibling Rivalry pada anak usia sekolah Kelas V dan VI SD Darul Faizin. Jenis penelitian adalah kuantitatif, dengan desain cross sectional. Sampel adalah siswa sekolah dasar kelas V dan VI sebanyak 30 orang. Pengumpulan data menggunakan kuesioner pola asuh dan Sibling Rivalry. Didapatkan hasil Kurang dari setengahnya (43,3%) anak sekolah dasar Kelas V dan VI mendapatkan pola asuh dengan model pola asuh mengabaikan (permisif), Lebih dari setengahnya (56,7%) anak sekolah dasar Kelas V dan VI dengan Sibling Rivalry. Maka dapat disimpulkan Ada hubungan pola asuh orang tua dengan Sibling Rivalry pada anak usia sekolah Kelas V dan VI SD Darul Faizin (pvalue= 0,02). Diharapkan Orang tua mengikuti penyuluhan tentang pola asuh anak sehingga dapat memahami pola pengasuhan anak yang baik agar anak dapat tumbuh kembang dengan baik.